1975
DOI: 10.1902/jop.1975.46.7.387
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Immunoglobulins IgG, IgA, and IgM in the Human Inflamed Gingiva

Abstract: Resected inflamed gingival tissue obtained from 16 periodontal patients and a pooled sample of noninflamed gingiva from five edentulous patients were assayed for immunoglobulins IgG, IgA, and IgM using low-level immunodiffusion plates. Findings based on the gingival assays include:(1) IgA and IgG are present in both inflamed and normal gingiva and although their levels are substanitally higher in the inflamed gingiva, their ratio, one to another, remains the same; (2) IgM can not be consistently demonstrated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…The predominance of IgG confirmed the findings of previous studies which utilized immunofiuorescent investigation of inflamed gingiva (Brandtzaeg & Kraus 1965, Genco et al 1974, Mackler et al 1977. Further, the proportion of IgG found was similar to that reported in previous studies which utilized gingival homogenates (Byers et al 1975, Gross et al 1979, Van Swol et al 1980 or supernatants taken from gingival fragment cultures (Steubing et al 1979). As compared with immunofluorescent, gingival homogenate, and gingival fragment culture studies, an advantage of the cell recovery technique employed in the present investigation was that it permitted accurate quantitation of the amount of immunoglobulin secreted in vitro by a known number of lymphocytes recovered from inflamed gingiva.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The predominance of IgG confirmed the findings of previous studies which utilized immunofiuorescent investigation of inflamed gingiva (Brandtzaeg & Kraus 1965, Genco et al 1974, Mackler et al 1977. Further, the proportion of IgG found was similar to that reported in previous studies which utilized gingival homogenates (Byers et al 1975, Gross et al 1979, Van Swol et al 1980 or supernatants taken from gingival fragment cultures (Steubing et al 1979). As compared with immunofluorescent, gingival homogenate, and gingival fragment culture studies, an advantage of the cell recovery technique employed in the present investigation was that it permitted accurate quantitation of the amount of immunoglobulin secreted in vitro by a known number of lymphocytes recovered from inflamed gingiva.…”
Section: Discussionsupporting
confidence: 89%
“…Two drawbacks with immunofluorescent studies are that serum-derived immunoglobulins permeating through the gingival connective tissue may bind cytophilically to lympboid cells via the Fc receptor (Mackler et al 1978) and that detection of intracellular immunoglobulin does not reflect the secretory capacity of B lymphocytes (Gitlin & Sasaki 1969). In studies of gingival homogenates (Byers, Toto & Gargiulo 1975, Gross etal. 1979, Van Swoletal.…”
Section: Introductionmentioning
confidence: 99%
“…This result was similar to the reports of other investigators (Hrodek et al 1984, Naito et al 1985 The comparative study of the antibody responses of GCF and homologous serum in the patients diagnosed as having elevated serum antibody responses against the antigens tested suggested the possibility that there is local synthesis of antibody by the gingival cells in the sites showing disease activity. Other studies have also demonstrated possible local antibody synthesis by the gingival cells (Marttala et al 1974, Byers et al 1975, Tew et al, 1985. Martin et al, (1986) also reported elevated levels of immunoglobulins in the gingival tissue supernatant fluid reactive to B. gingivalis in rapidly progressive patients as compared with other adult periodontitis patients.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of local antibodies in inflamed human gingiva has been documented (Hartzer, Toto, and Gargiulo, 1971, Byers, 1973, Marttala, Toto, and Gargiulo, 1974.…”
Section: Cervicoradicular Infections Have Been Induced In Rodents Bymentioning
confidence: 99%